2011
DOI: 10.2147/jpr.s17882
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain as a process: reversal of chronification in an animal model

Abstract: Peripheral neuropathic pain arises from trauma to sensory nerves. Other types of acute neurotrauma such as stroke and spinal cord injury are treated immediately, largely to prevent secondary damage. To pursue the possibility that neuropathic pain may also be amenable to early treatment, a rat model of neuropathic pain was induced using a 2-mm polyethylene cuff implanted around one sciatic nerve. Within 24 hours, hypersensitivity to von Frey hair stimulation appeared, as indicated by decreased paw withdrawal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The test equipment included a standard plastic box for open-field and novel-object recognition tests and O-maze and Y-maze apparatus from Phenome Technologies. Tests were conducted as we described previously (Coutellier and Usdin, 2011;Coutellier et al, 2011). Time spent in the central 50% of the open field, time spent in the O-maze open arms, and the number of Y-maze spontaneous alternations are presented as a percentage of the total time (5 min in each case) or total number of entries.…”
Section: Methodsmentioning
confidence: 99%
“…The test equipment included a standard plastic box for open-field and novel-object recognition tests and O-maze and Y-maze apparatus from Phenome Technologies. Tests were conducted as we described previously (Coutellier and Usdin, 2011;Coutellier et al, 2011). Time spent in the central 50% of the open field, time spent in the O-maze open arms, and the number of Y-maze spontaneous alternations are presented as a percentage of the total time (5 min in each case) or total number of entries.…”
Section: Methodsmentioning
confidence: 99%
“…Therapeutic interference within the consolidation process may fully prevent the development of lasting (e.g., neuropathic) pain. For example, when neuropathic pain is induced in rats by placing a cuff around the sciatic nerve, mechanical hyperalgesia develops within 24 h. Removal of the cuff 24 h but not 4 days after implantation allows full recovery of mechanical thresholds within 18 days [21]. Likewise, a single intrathecal injection of GABA apparently reverses neuropathic pain permanently when given 1 week after a chronic constriction injury of the sciatic nerve in rats, but not when given more than 2–3 weeks after the injury [22].…”
Section: Memory Traces Of Painmentioning
confidence: 99%
“…This brief and reversible neurologic deficit was identical to the findings using the acute nerve crush or clip model, with spontaneous full recovery after injury [ 19 , 20 ]. Dableh et al [ 5 ] reported that the tactile hypersensitivity induced by temporary mechanical compression can be spontaneously reversed by removing the implanted perineural cuff of the sciatic nerve. They revealed that removal of the cuff at 24 h after hypersensitivity induction led to full recovery to the baseline threshold, whereas removal of the cuff after 4 days demonstrated only partial alleviation.…”
Section: Discussionmentioning
confidence: 99%
“…If the external compression forces persist, subsequent muscle weakness and atrophy will gradually develop with time, increasing in severity [ 4 ]. With the increase in local compression forces, ischemia of the surrounding connective tissue and nerves might trigger a subsequent cascade of nerve damage and prolonged neuroinflammation [ 5 , 6 ]. The initial histopathological changes of compressive neuropathy induce a breakdown of the blood–nerve barrier and subperineurial edema [ 7 ].…”
Section: Introductionmentioning
confidence: 99%